Public Engineering of Party and Electoral Systems Development in the Russian Federation - О. N. Shalashova (Управленческое консультирование)
The purpose of this article is to substantiate the key elements of public administration design of party and electoral systems development, namely, legislative, financial and communication technologies. The paper proves that qualitative, manageable, change in young democracy must inevitably be designed at the state level. Party and electoral systems are not only subject to spontaneous development, but can also be purposefully developed based on the goals and objectives of public administration. The key research issue in this paper is to identify factors that can hinder the processes of development and institutionalization of party and electoral systems in the Russian Federation. Theoretical basis of the study was formed by D. P. Quintal, G. Sartori, R. Taagepera, M. S. Shugart, K. Benoit and E. Laszlo. The application of political theories helped to prove the relevance of studying the party system as an important part of the political sphere, as well as to demonstrate the importance of the selected public engineering elements. The review of the practice of electoral and party institutes in the Russian Federation, based on theoretical analysis, helped to understand what are the features of state public engineering in this area. On the basis of the theoretical analysis, a number of conclusions were made about the validity of certain measures of state influence on the party and electoral systems. The public engineering for last half a century has gained special value from the point of view of development of political system as a whole and electoral system in particular. In the strategic plan, the public engineering of the development of the party and electoral system should be based on working with young people as a projective object of public management. The main factors that potentially have a negative impact on the development and institutionalization of party and electoral systems include the following: (1) the absence of a systematic approach to changes in legislation; (2) the absence of a comprehensive system of feedback from the electorate, which leads to sustainable absentism and may harm the very system of public engineering of party and electoral systems; (3) the unresolved problem of content management in the campaigns of political parties, as a result of which most campaigns are based on the promotion of leaders known to all, which is poorly aligned with the demand of young people for new political actors; (4) the lack of a comprehensive system of feedback from the electorate.